Vitamin D Dependent Rickets Type 1A Caused by Mutation - Na Ry Bak; Eun Song Song; Eun Mi Yang; Chan Jong Kim (Korean Society of Pediatric Nephrology, 2019)
Vitamin D dependent rickets type 1A (VDDR1A) is an autosomal recessive disorder caused by mutations in CYP27B1 . Clinical findings are growth retardation, hypotonia, muscle weakness, hypocalcemic seizures, and radiological features of rickets. We aimed to present the VDDR1A case with a genetic study of CYP27B1 . The 14-month-old boy was admitted to the hospital due to a seizure. Serum calcium, phosphorus, alkaline phosphatase, parathyroid hormone (PTH), 25(OH) vitamin D, and 1,25(OH)2 vitamin D values were 5.1 mg/dL, 3.7 mg/dL, 705 IU/L, 429 pg/mL, 24.9 ng/mL, and 8.8 pg/mL, respectively. Radiological study showed cupping and fraying of the distal ulna and radius. The molecular genetic study revealed that the patient had a compound heterozygous mutation, Phe443Profs*24 and c.589+1G>A, in CYP27B1 . Genetic analysis of the family members presented that the mother was heterozygous for the mutation c.589+1G>A, and that the father was heterozygous for Phe443Profs*24. The patient was treated with calcium lactate and calcitriol. Until now, six Korean patients with VDDR1A have been studied. Including this case, Korean patients with VDDR1A were found to have only three different mutations in 14 alleles, indicating that the mutation in the CYP27B1 gene is homogeneous in the Korean population.